Microscale anechoic architecture: acoustic diffusers for ultra low power microparticle separation via traveling surface acoustic waves. Issue 1 (24th October 2014) - Behrens, Jan; Langelier, Sean; Rezk, Amgad R.; Lindner, Gerhard; Yeo, Leslie Y.; Friend, James R.
Abstract : A versatile, low-power traveling wave SAW microfluidic sorting device using a Schröder diffuser, adopted from its typical use in concert halls to the microscale. Abstract : We present a versatile and very low-power traveling SAW microfluidic sorting device able to displace and separate particles of different diameter in aqueous suspension; the travelling wave propagates through the fluid bulk and diffuses via a Schröder diffuser, adapted from its typical use in concert hall acoustics to be the smallest such diffuser to be suitable for microfluidics. The effective operating power range is two to three orders of magnitude less than current SAW devices, uniquely eliminating the need for amplifiers, and by using traveling waves to impart forces directly upon suspended microparticles, they can be separated by size.